Childhood vulnerabilities in South Africa some ethical perspectives - Grobbelaar, Jan; Jones, Chris (Stellenbosch African Sun Media, 2021)
Intro -- CONTENTS -- RESEARCH JUSTIFICATION -- LIST OF ABBREVIATIONS APPEARING IN THE TEXT AND NOTES -- PREFACE -- Editors -- NOTES ON CONTRIBUTORS -- 1. The plight and vulnerability of children living in South Africa and the calling of the Church -- 2. Seen but not heard? Engaging the mechanisms of faith to end violence against children -- 3. The contentious issue of corporal punishment in South Africa -- 4. Reconceiving child theology from a queer theological perspective: for LGBTIQ+ parented families and children -- 5. The stigmatisation of children living with FASD and their biological mothers -- 6. Male initiation and circumcision - A South African perspective -- 7. Recognising and responding to complex dilemmas: Child marriage in South Africa -- 8. Children and racism -- 9. Reflections on the effectiveness of child support grants -- 10. Protecting children in the digital society -- REFERENCES.
Description based on publisher supplied metadata and other sources
Keywords: Children-Institutional care; Church work with children; Children-Religious life-South Africa; Electronic books; Südafrika